Identity Management Strategies for Workers with Concealable Disabilities: Antecedents and Consequences. (9th April 2019) - Santuzzi, Alecia M.; Keating, Robert T.; Martinez, Jesus J.; Finkelstein, Lisa M.; Rupp, Deborah E.; Strah, Nicole
Abstract: Twenty‐eight currently or recently employed adults with concealable impairments from a community in the United States completed semi‐structured interviews to capture workers' perceptions of their internal and social experiences that contribute to their identity management decisions. Disability identity management strategies included effortful behaviors, such as avoiding relevant situations and using specific language to describe impairments. Participants suggested intraindividual factors (disability salience, disability strain) and environmental factors (disability stigma, ineffective social support) as primary reasons for their identity management decisions. The findings align with existing research on stigmatized identity management and consequences for well‐being, together informing a proposed theoretical model. Conclusions invite policy change at national and organizational levels to account for intraindividual and environmental factors that may introduce barriers to disability disclosure and effective accommodation practices.